Changes in Glucose Breath Test in Cystic Fibrosis Patients Treated With 1 Month of Lumacaftor/Ivacaftor. Issue 1 (20th April 2022) - Gabel, Megan E.; Wang, Hongyue; Gelfond, Daniel; Roach, Christine; Rowe, Steven M.; Clancy, John P.; Sagel, Scott D.; Borowitz, Drucy; ,
Abstract : Background: Alteration of the airway microbiota is a hallmark of cystic fibrosis (CF) pulmonary disease. Dysfunction of cystic fibrosis transmembrane regulator (CFTR) in the intestine also promotes changes in local microbiota such as small intestinal bacterial overgrowth (SIBO), which is common in CF. We evaluated whether therapy with the CFTR modulator combination lumacaftor/ivacaftor (luma/iva) has a beneficial impact on SIBO as measured by breath testing (BT). Methods: A multicenter longitudinal study of CFTR-dependent disease profiling (NCT02477319) included a prospective evaluation for SIBO by BT. Tidal breath samples were collected after fasting and 15, 30, 45, 60, 90, and 120 minutes after ingestion of glucose, before and 1 month after subjects initiated luma + iva. Results: Forty-two subjects enrolled in the sub-study (mean age = 23.3 years; 51% female; 9.5% Latinx); 38 completed a hydrogen BT at both time points, of which 73.7% had a positive BT before luma/iva (baseline) and 65.8% had a positive test after luma/iva ( P = 0.44); shifts from negative to positive were also seen. Use of azithromycin (63.1%) and inhaled antibiotics (60.5%) were not associated with positive BT. Acid-blocking medications were taken by 73% of those with a negative BT at baseline and by 35% with a positive baseline BT ( P = 0.04). Conclusion: We found a high rate of positive hydrogen breath tests in individuals with CF, confirming that SIBO is common. One month of luma/iva did not significantly change the proportion of those with positive breath hydrogen measurements.